Political Oversight and Intervention in the Policy for the Allocation of the Special Autonomy Fund for Aceh - Hidayat, Fauzan (Bestuurskunde: Journal of Governmental Studies, 2022)
Problems in planning readiness that have not been optimally arranged in the Master Plan for Utilization of Special Autonomy Fund (DOKA) 2008—2027 are the cause of the difficulty in carrying out an effective supervisory function. In addition, at the level of DOKA allocation at the Provincial to Regency/City levels, it is still full of intervention and domination by ex-members of Free Aceh Movement (GAM), both in the executive and legislative. These two problems are the main factors that hinder the achievement of the goal of the DOKA for the welfare of the Acehnese people. By using a qualitative descriptive research method, this paper aims to unravel the root cause of the DOKA allocation problem that has an impact on the problem of poverty in Aceh. The results of this study conclude that there are two factors that cause problems in the allocation of DOKA, namely supervision and political intervention. The control factor that is not optimal is caused by planning that has not been arranged in detail in the DOKA Master Plan. Meanwhile, the political intervention factor arises from the dominance of ex members of GAM in every DOKA budget planning.